1997
DOI: 10.1007/bf03339945
|View full text |Cite
|
Sign up to set email alerts
|

Selective processing of eating and body words in restricting-type anorexics, binge-eating-type anorexics, bulimics, and control subjects

Abstract: A French adaptation of the Stroop colour-naming task was used to investigate selective processing of information related to eating and the body in 92 female subjects: 18 with restricting-type anorexia nervosa (RAs), 25 with binge-eating-type anorexia (BAs), 20 with bulimia nervosa (BNs), and 29 controls (Cs). All participants were significantly slower in colour-naming words related to eating and the body. This suggests that eating and body Stroop effects were not diagnostic category effects. Eating Stroop effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
3
3
Order By: Relevance
“…The EDI-2 Drive for Thinness did not correlate with the results of the Stroop test or the WCST. These results contrast, as in other studies (Leonard et al, 1997), with the hypothesis that a high score in the area of eating pathology may influence the process of selection of information connected with food or body size (Perpina et al, 1993).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The EDI-2 Drive for Thinness did not correlate with the results of the Stroop test or the WCST. These results contrast, as in other studies (Leonard et al, 1997), with the hypothesis that a high score in the area of eating pathology may influence the process of selection of information connected with food or body size (Perpina et al, 1993).…”
Section: Discussioncontrasting
confidence: 83%
“…These data seem to differ somewhat from those described in previous studies (Chesters et al, 1998;Cooper & Fairburn, 1994;Cooper & Todd, 1997;Green, McKenna, & De Silva, 1994;Perpina, Hemsley, Treasure, & De Silva, 1993), whereas they are in accord with data found by other authors (Ben-Tovim et al, 1989;BenTovim & Walker, 1991;Leonard, Divac, Bichindaritz, Rouer-Saporta, & Samuel-Lajeunesse, 1997). These authors observed that the Stroop effect in patients appears in some cases in response to the food stimulus words (eating) and in other cases in response to words regarding the body (body).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Further, all but one of the available effect sizes across both significant and non-significant findings (Black et al, 1997) indicated greater AB to food in women with BN. No differences were found in AB to food cues between women with BN vs. AN-B/P (Léonard et al, 1997) or between women with threshold vs. subthreshold BN (Lokken et al, 2006). …”
Section: Resultsmentioning
confidence: 87%
“…Among studies using the Stroop task with food-related cues, the majority of studies found no significant differences in AB between women with BN and healthy controls (Black, Wilson, Labouvie, & Heffernan, 1997; Davidson & Wright, 2002; Flynn & McNally, 1999; Johansson, Carlbring, Ghaderi, & Andersson, 2008; Lee, Namkoong, & Jung, 2017; Lovell, Williams, & Hill, 1997; Perpiñá, Hemsley, Treasure, & de Silva, 1993; Perpiña, Leonard, Treasure, Bond, & Banos, 1998; Ruiz, de Leon, & Diaz, 2008; Waller & Ruddock, 1995), and six studies indicated that women with BN had greater AB to food cues compared to healthy controls (Ben-Tovim & Walker, 1991; Ben-Tovim, Walker, Fok, & Yap, 1989; Cooper & Todd, 1997; Jones-Chesters, Monsell, & Cooper, 1998; Léonard, Divac, Bichindaritz, Rouer-Saporta, & Samuel-Lajeunesse, 1997; Lokken, Marx, & Ferraro, 2006). Further, all but one of the available effect sizes across both significant and non-significant findings (Black et al, 1997) indicated greater AB to food in women with BN.…”
Section: Resultsmentioning
confidence: 99%